Gender comparison in EMG amplitude during maximal voluntary contractions of the upper limb muscles - Tan, Tian Xiang (2016)
In earlier studies of Electromyography (EMG), many researchers used surface Electromyography (sEMG) to investigate the relationship between the EMG signal and the muscle activation among males and females. The purpose of this study is to compare the EMG amplitude on upper limb muscles (Biceps and Forearm) during maximal voluntary contractions (MVC) of isometric exercise between males and females. Ten right hand dominant (5 male and 5 female) subjects with different anthropometric characteristics participated in the experiment. The participants performed isometric contractions by gripping the hand dynamometer at 50%, 75%, and 100% of their MVC. This EMG analysis was carry through in the time domain by calculating the amplitude of the EMG signals in root mean square (RMS) and mean absolute value (MAV). The statistical analysis included linear regression to examine the relationships between the EMG signals (mV) and the force value exerted by males and females. The 2 sample t-test about the value of RMS and MAV with force value was performed in Minitab to test the significance among these variables. The calculation of mean, standard deviation and coefficient of variation (CoV) to describe the dispersion of the variables and the steadiness of the EMG signals between genders. The results disclose that the regression analysis of the EMG with the force exerted by male subjects (R2 = 0.890, P-value < 0.05) during isometric contraction was greater than that obtained from female subjects (R2 = 0.678, P-value < 0.05). In addition, the EMG signals generated by male forearm muscle (3.16%) express less variability than that generated by female forearm muscles (4.21%). This EMG data analysis results can provide useful information for the analysis and further study in the fields of medical research, rehabilitation engineering and health technology. Last but not least, this results is also contribute to the developing of prosthesis hand or robotic arm and the biomechanics movements of males and females.